Analisis Biaya Kerugian pada Kemacetan Akibat Perlintasan Kereta Api Ditinjau dari Konsumsi Bahan Bakar Minyak Di Kota Bandar Lampung (Studi Kasus : Jalan H. Komarudin) - Laksono, Bambang Tri; Sulistyorini, Rahayu; Ofrial, Siti Anughrah Mulya Putri; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
This study aims to determine the value of the loss of fuel consumption in traffic jams due to railroad crossings on Haji Komarudin Street. Some of the data needed to calculate the value of the loss include: traffic volumes, time and vehicle mileage per liter of fuel, traffic jam time, vehicle travel time, annual car sales data and the price of each type of fuel per liter. The results of this study are greatly influenced by the volume of vehicles, traffic jam time and fuel price.For the direction  of Haji Komarudin Street – K.A.Haq Street,  obtained  the value of the loss on the motorcycle of Rp396.254.902 per year, gasoline-powered light vehicles of Rp404.825.040 per year, diesel-fueled light vehicle of Rp27.253.571 per year, heavy vehicle of Rp3.886.377 per year. As for directions K.A.Haq Street – Haji Komarudin Street  losses on motorcycles amounted to Rp256.301.247 per year,   gasoline-powered light vehicles of Rp284.150.353 per year,   diesel- fueled light vehicle of Rp19.151.351 per year and heavy vehicle of Rp2.037.824 per year. Key words: Haji Komarudin Street, loss cost,  fuel consumption, congestion.